Apostolic Process on John Nepomucene Neumann in the Diocese of Budweis 1897-1901 - Rudolf Svoboda (Kościół i Prawo)
The process of the canonization and beatification of John Nepomucene Neumann began in 1886 in the Archdiocese of Philadelphia and the Diocese of Budweis. His canonization was completed in 1977. The study presents an as yet uncharted topic of the apostolic process in the Diocese of Budweis in 1897-1901 and other activities and events related to Neumann’s process of beatification and canonization in the Diocese Budweis until the decree on Neuman’s heroic virtues was issued in 1921.